Literature Review: Pola Makan Dan Aktivitas Fisik Pada Obesitas Remaja - Vionie Putri Istiqomah Istiqomah; Novera Herdiani (PROSIDING NATIONAL CONFERENCE FOR UMMAH, 2020)
Obesity is a disease characterized by excessive storage of fat in fat tissue in the body. Obesity is becoming a health problem in the world and the increasing prevalence of adolescent obesity in both developed and developing countries. Adolescent obesity is important to note because the period of growth and development can change rapidly so that it affects the development of body composition and changes in weight. This study aims to find out the link between diet and physical activity in adolescent obesity. The research method uses traditional literature review, with the source of Google Scholar articles there are 9,990, Garuda Portal there are 24 and Pubmed there are 463 with a range of 2016-2020. Keywords are used in searches for articles "diet of obese adolescents", "physical activity of obese adolescents" and "eating patterns and physical activity and obesity and teenagers". The results of the article are 12 referenced in literature review writing and then analyzed using illustrative methods. Diet in adolescent obesity is obtained from macro nutrient intake, frequency of eating, eating fast food and breakfast habits. Teen physical activity is done in light categories such as watching TV, reading books, and walking. Youth activities are varied but do not pay attention to the recommended quantity. The conclusion is that overeating and lack of physical activity lead to obesity in adolescents. Health advice provides knowledge regarding a balanced diet and healthy lifestyle, for teenagers expected to eat a balanced diet and exercise routine.